Cardiorenal ketone metabolism: a positron emission tomography study in healthy humans - Cuenoud, Bernard; Croteau, Etienne; St-Pierre, Valérie; Richard, Gabriel; Fortier, Mélanie; Vandenberghe, Camille; Carpentier, André C.; Cunnane, Stephen C. (Frontiers in Physiology, 2023)
Ketones are alternative energy substrates for the heart and kidney but no studies have investigated their metabolism simultaneously in both organs in humans. The present double tracer positron emission tomography (PET) study evaluated the organ distribution and basal kinetic rates of the radiolabeled ketone, 11C-acetoacetate (11C-AcAc), in the heart and kidney compared to 11C-acetate (11C-Ac), which is a well-validated metabolic radiotracer. Both tracers were highly metabolized by the left ventricle and the renal cortex. In the heart, kinetic rates were similar for both tracers. But in the renal cortex, uptake of 11C-Ac was higher compared to 11C-AcAc, while the reverse was observed for the clearance. Interestingly, infusion of 11C-AcAc led to a significantly delayed release of radioactivity in the renal medulla and pelvis, a phenomenon not observed with 11C-Ac. This suggests an equilibrium of 11C-AcAc with the other ketone, 11C-D-beta-hydroxybutyrate, and a different clearance profile. Overall, this suggests that in the kidney, the absorption and metabolism of 11C-AcAc is different compared to 11C-Ac. This dual tracer PET protocol provides the opportunity to explore the relative importance of ketone metabolism in cardiac and renal diseases, and to improve our mechanistic understanding of new metabolic interventions targeting these two organs.